An integrated Data Envelopment Analysis (DEA)/ Fuzzy AHP/ Assurance Region (AR) method in measuring efficiency of life insurance companies in Malaysia / Nur Azlina Abd Aziz ... [et al.] - Abd Aziz, Nur Azlina; Mohd Hashim, Bikriah Bakraj; Khairil Anwar, Dhia Azeem; Fairul Rafiq, Farah Hazwani (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
Despite the challenging business environment caused by COVID-19, the insurance sector has continued to contribute to Malaysia's economic growth as one of the most significant and dominating financial services in the country (Drake, 2014). The largest threat to the insurance industry, according to Bank Negara Malaysia, is rising competition. Therefore, in order to remain competitive, the companies need to measure their performance and efficiency consistently. Data Envelopment Analysis (DEA) has been used widely in many applications in evaluating the efficiency of decision-making units (DMUs). The main advantage of the DEA method is it can handle multiple inputs and outputs simultaneously. However, there are some drawbacks that resulting from it, which are poor discrimination power and unrealistic weight such as zero weights which affects accuracy of the efficiency results (Bal et al., 2010). In this study, Data Envelopment Analysis (DEA) method is integrated with Fuzzy Analytic Hierarchy Process (Fuzzy AHP) and Assurance Region (AR) to overcome the drawbacks. Therefore, the aims of this study are to improve discrimination power and reduce zero weights assigned to inputs/outputs by adopting the integrated method DEA/Fuzzy AHP/AR and applies it in evaluating the efficiency of 12 life insurance companies in Malaysia.